Dalle esigenze alle opportunità - Michele Ercolini (Firenze University Press, 2021)
This book sets itself specific objective: namely, the consideration of the design of the river landscape as a cultural and social investment. The aim is at "control" of a landscape which is transformed while preserving harmonious forms and structures that are sustainable from an ecological and environmental aspect, and is continually redesigned on the basis of human requirements, without overwhelming nature. The need for hydraulic defence of the rivers thus becomes an opportunity for a "third landscape" project, a chance to transform "non-places" into "places".